PERLINDUNGAN HUKUM ATAS PEMBERHENTIAN PEGAWAI NON ASN PADA PERGURUAN TINGGI NEGERI SEBELUM MENGIKUTI SELEKSI PPPK - Utama MS, Robby Yunianto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The unilateral dismissal of permanent non-civil servant employees (non-ASN) working under Public Service Agencies (BLU) constitutes an act that should be declared legally invalid. Such action contradicts the principles of justice, legal certainty, protection of employees’ rights, and the principles of good governance. This dismissal not only violates the normative rights of employees as regulated in the Manpower Law and the State Civil Apparatus Law but also infringes upon the constitutional right to decent work as guaranteed under Article 27 paragraph (2) of the 1945 Constitution. Moreover, the dismissal process carried out without verification, dialogue, validation, or the provision of transitional arrangements represents a neglect of the institution’s legal responsibilities, potentially leading to injustice and both material and immaterial losses for employees. Therefore, the dismissal decision should be annulled or reviewed, and Higher Education Institutions are obliged to provide a fair transition opportunity for non-ASN employees, including the right to participate in the PPPK recruitment process, in accordance with the prevailing laws and regulations.Keywords: Legal Protection, Non-ASN Employees, PPPK.